COVID-19 convalescent plasma for B-cell depleted patients: a systematic review and individual patient data meta-analysis - Zaremba, Solomiia; Focosi, Daniele; Pruter, Wyatt W.; Franchini, Massimo; Collantes Hoyos, Diana B.; Cruciani, Mario; Miller, Alex J.; Ripoll, Juan G.; Casadevall, Arturo; Tulledge-Scheitel, Sidna M.; Rufer, Nathalie; Hueso, Thomas; et al. (Frontiers in Medicine, 2025)
COVID-19 convalescent plasma (CCP) obtained from recently recovered people is safe and effective against SARS-CoV-2. Currently available CCP is a “hybrid” product with antibodies from individuals who had both infection and vaccination (vaccine-boosted CCP). B-cell depleted patients are at risk of not producing antibodies after either infection or vaccination, hence conceivably among those who would benefit the most from CCP. We thus conducted a systematic review and individual participant data meta-analysis to assess characteristics associated with 60-day survival in B-cell depleted patients transfused with CCP. The protocol was registered with PROSPERO (CRD42024516513) on March 1st, 2024. The last search was on April 2nd, 2024, and included all studies using CCP in B-cell depleted patients. Whenever not available, we requested individual participant data from corresponding authors of eligible studies. Risk of bias was assessed using Joanna Briggs Institute Critical Appraisal Tools. Data were analyzed using conditional logistic regression. The overall 60-day survival rate was 86.5% in our cohort of 570 patients (85 included studies). After controlling for age, sex, calendar year of infection and World Health Organization (WHO) disease severity, we found a significant association between 60-day survival and transfusion of vaccine-boosted CCP (OR = 9.49; 95% CI 2.01–44.82; p = 0.005). Overall survival in our cohort of B-cell depleted patients was consistent with prior meta-analysis of randomized controlled trials on survival of immunocompromised patient transfused with CCP (~84%). A novel finding from this analysis is that vaccine-boosted CCP is associated with a high survival benefit.